Composição e variabilidade química dos óleos essenciais das folhas e frutos de Eugenia dysenterica - Duarte, Alessandra Rodrigues (2008)
The chemical variations in the essential oil compositions of the wild and cultivated Eugenia dysenterica DC. (Myrtaceae) populations indicated the presence of two clusters of oils according to sampling origin. The cluster I included cultivate (subcluster IA) and mainly wild samples (subcluster IB) originating from Senador Canedo (SC), with high percentages of a-pinene (9.0 ± 2.3%), b-pinene (9.3 ± 2.6%), (Z)-b-ocimene (5.9 ± 4.2%) and g-cadinene (27 ± 5%), limonene (12 ± 9%), and caryophyllene oxide (7.4 ± 4.7%), respectively. In cluster II, with wild and cultivated samples originating from Campo Alegre de Goiás, the major constituents were b-caryophyllene (24 ± 8%), d-cadinene (13 ± 4%), and a-copaene (9.6 ± 3.2%). The canonical correlation analysis revealed that limonene, ?-cadinene, caryophyllene oxide, Zn, Cu, Fe, Mn, and mean monthly values of temperature and precipitation were quite strongly related to SC wild samples (subcluster IB), whereas (Z)-b-ocimene, a-copaene, b- caryophyllene, a-humulene, d-cadinene, and P were related to wild samples from CA and cultivated samples, regardless of population origin (subcluster IA and cluster II). Sesquiterpene hydrocarbons predominated in all population sampled and the observed essential oil chemovariation might be genetically determined (chemotypes), in addition to a clear environmental influence on the samples originating from SC site (ecotypes). Chemical variations in essential oil compositions of cultivated E. dysenterica populations in dry and wet seasons have indicated the presence of two oil clusters related to sampling origin and seasons. Cluster I included dry (subcluster IA) and mainly wet samples (subcluster IB) originating from Senador Canedo (SC), with high percentages of b-pinene?(9.3 ± 2.6%), a-pinene (9.0 ± x 2.3%), (Z)-b-ocimene (5.9 ± 4.2%) and g-cadinene (17 ± 11%), limonene (14 ± 9%), and b-pinene?(8.6 ± 5.4%), respectively. In cluster II, which included dry and wet cultivated samples originating from Campo Alegre de Goiás, the major constituents were b-caryophyllene (32 ± 15%), d-cadinene (13 ± 6%), and a- copaene (8.1 ± 4.0%). Here also, sesquiterpene hydrocarbons predominated in all the sampled populations and the observed essential oil chemovariation might be genetically determined, in addition to a clear seasonal influence only on the samples originating from the SC site. In addition, the oils from wild E. fruits harvested during three stages of ripening showed the monoterpene hydrocarbons as most abundant group of volatiles, accounting for about 68% of the total identified compounds. Limonene (25.8% and 24.6%), (E)-b-ocimene (20.3% and 21.7%) and b-pinene (12.0% and 14.2%) were the compounds in the unripe and semi-ripe stages, respectively, while g-muurolene (25.8%), b-caryophyllene (18.4%) and a- humulene (15.4%) became the major compounds in ripe fruits. The concentration of monoterpenes was high in the unripe and semi-ripe stages and decreased afterwards, while sesquiterpenes were intensively synthesized only in the last part of the ripening process.